The category of fact in the analytic philosophy of the XX – beginning XXI centuries (Actual Problems of Mind, 2017)
The article considers the most significant conceptions of the facts in the works bz analytic philosophers: Frege, Wittgenstein, Russell, Baylis, Ramsey, Davidson, Neale, Armstrong and Mulligan. Concepts are ranged by their views on the nature, function, ontological status and determining of the fact.
Keywords: Fact; concept of facts; analytical philosophy; philosophical category; state of affairs